Determinants of societal costs in Alzheimer's disease: GERAS study baseline results. Issue 8 (3rd April 2015) - Dodel, Richard; Belger, Mark; Reed, Catherine; Wimo, Anders; Jones, Roy W.; Happich, Michael; Argimon, Josep M.; Bruno, Giuseppe; Vellas, Bruno; Haro, Josep Maria
Abstract: Background: To identify the main factors associated with societal costs of Alzheimer's disease (AD) in community‐dwelling patients across three European countries. Methods: Baseline cost data from a prospective, observational study were used. Assessments included patients' cognition, activities of daily living (ADLs) and behavioral symptoms, and caregiver burden. Cost calculations (2010) from the societal perspective were based on patient/caregiver resource use. Generalized linear models estimated factors associated with costs. Results: Mean monthly costs per patient differed for France (€1881), Germany (€2349), and the UK (€2016), with informal care costs accounting for 50% to 61%. Independent factors associated with costs across all countries were ADL total score, patient living arrangements, caregiver working status, and caregiver burden (all P  < .05). Additional factors were significant for the pooled cohort or individual countries. Conclusions: Several patient and caregiver factors, including factors associated with informal care, should be included when evaluating care options for patients with AD.